A case of severe hypothermia with acute suppurative cholangitis resulting in bradycardia and cardiac arrest during rewarming - Ikeda, Mayuko; Hirose, Yosuke; Yuzawa, Hiroko; Kondo, Kengo; Hosono, Kazuki; Sadahiro, Tomohito (KANTO Journal of Japanese Association for Acute Medicine, 2022)
A 74-year-old man with severe hypothermia complicated by septic shock due to acute suppurative cholangitis was admitted to our hospital in an unconscious state. On admission, his rectal temperature was 26.7 ℃, systolic blood pressure was 57 mmHg and ECG showed sinus bradycardia at 49 beats/min. Large volumes of warm intravenous fluid were administered, but the patient went into cardiac arrest twice during warming. Cardiopulmonary resuscitation was promptly performed, and spontaneous circulation was restored twice. Hypothermia, especially in the elderly, should be treated urgently by suspecting infection and investigating the cause as well as restoring body temperature. In addition, during the treatment of hypothermia, it is necessary to keep in mind that not only VT/VF but also cardiac arrest may occur during warming.